Plan de mercadeo para mejorar las ventas de super despensa Polita del cantón Buena Fe, año 2015. - Ramírez Quijije, Gáster Colón (2016)
This research project was made to design a marketing plan in Super Pantry Polita Canton Buena Fe, Los Rios province, 2015, in order to meet the tastes and preferences when making purchases in local which retailed food products with the development of the marketing plan greater influx of customers projected expending a variety of products with suitable prices encouraging saving consumers and maintain relationship with existing actual competition through the research design it was determined the population between 18 to 65 years getting 43,306 people surveyed in the canton Buena Fe, with a sample corresponding to 396 surveys, deductive methods are also used to establish the conclusions of the results of the surveys, it was prepared an interview addressed to the owner to know the current situation of the company that indicated the lack of marketing strategies to market the products within the target market which clearly indicates the lack of a marketing plan reflecting a negative marketing in the products sold which leads to get some positioning in the target market so it should be emphasized that 100% of the inhabitants of the canton Buena Fe buy consumer products, but in the Super Despenda Polita as customers feel little satisfied with 40% is therefore to be done by marketing mix strategies to market the products in order to attract and retain customers consumers consumer products and increasing sales volumes.